Modified Third Order Iterative Method for Solving Nonlinear Equations - Omran, Huda H (Al-Nahrain Journal of Science, 2018)
Many numerical approaches have been suggested to solve nonlinear problems. In this paper, we suggest a new two-step iterative method for solving nonlinear equations. This iterative method has cubic convergence. Several numerical examples to illustrate the efficiency of this method by Comparison with other similar methods is given.